Distinction between amorphous and healed planar deformation features in shocked quartz using composite color scanning electron microscope cathodoluminescence (SEM‐CL) imaging. (October 2016) - Hamers, Maartje F.; Pennock, Gill M.; Herwegh, Marco; Drury, Martyn R.
Abstract: Planar deformation features (PDFs) in quartz are one of the most reliable and most widely used forms of evidence for hypervelocity impact. PDFs can be identified in scanning electron microscope cathodoluminescence (SEM‐CL) images, but not all PDFs show the same CL behavior: there are nonluminescent and red luminescent PDFs. This study aims to explain the origin of the different CL emissions in PDFs. Focused ion beam (FIB) thin foils were prepared of specific sample locations selected in composite color SEM‐CL images and were analyzed in a transmission electron microscope (TEM). The FIB preparation technique allowed a direct, often one‐to‐one correlation between the CL images and the defect structure observed in TEM. This correlation shows that composite color SEM‐CL imaging allows distinction between amorphous PDFs on one hand and healed PDFs and basal Brazil twins on the other: nonluminescent PDFs are amorphous, while healed PDFs and basal Brazil twins are red luminescent, with a dominant emission peak at 650 nm. We suggest that the red luminescence is the result of preferential beam damage along dislocations, fluid inclusions, and twin boundaries. Furthermore, a high‐pressure phase (possibly stishovite) in PDFs can be detected in color SEM‐CL images by its blue luminescence.